Prevalence and viability of group A rotavirus in dairy farm water sources - Castells, M.L. (2018)
Aim: To analyse group A rotavirus (RVA) environmental contamination in waters used for calves' consumption and to assess viral viability in dairy farm water sources. Methods and Results: We analysed 202 samples of water used for calves' consumption and RVA was detected by RT‐qPCR in 35·1% (95% CI: 28·9–42·0%). A marked pattern of seasonality was observed with higher frequency of detection in colder than warmer months (P = 0·002). There was no association between viral load and season or between the number of milking cows in the herd and the detection of RVA in the farm. The viability of the RVA particles detected was confirmed by isolation of RVA in cell culture from 5 of 10 water samples. Furthermore, an RVA waterborne outbreak of neonatal calf diarrhoea was described. Conclusions: We demonstrate that RVA is frequent in dairy farm waters, and that the virus is infectious and capable of generating a diarrhoea outbreak. Significance and Impact of the Study: Neonatal diarrhoea syndrome leads to economic losses to the livestock industry worldwide. To determine transmission routes is essential to take action in this regard and reduce the impact that this syndrome has for the livestock production. The results obtained in this work alert the dairy industry and highlight that mitigation strategies are crucial to improve the microbiological quality of this water.